Characterization of Extruded Poly(lactic acid)/Pecan Nutshell Biocomposites - C. R. Álvarez-Chávez; D. L. Sánchez-Acosta; J. C. Encinas-Encinas; J. Esquer; P. Quintana-Owen; T. J. Madera-Santana (International Journal of Polymer Science)
Pecan nutshells are a solid form of waste obtained from the pecan nut production and they have been explored as an inexpensive filler for incorporation by melt blending into the poly(lactic acid) (PLA) matrix. The pecan nutshells contain polyphenols, proteins, tannins, sugars, and lipids; some of these components must be released in order to improve adhesion with a polymeric matrix. The physicochemical characterization of the extruded biocomposites of pecan nutshell powder (PNSP) at 0, 5, and 7.5% wt. with two treatments (untreated and defatted) into PLA is presented in this work. The incorporation of PNSP into the PLA matrix caused a variation in color and density and increased the water absorption. However, some mechanical and thermal parameters of the biocomposites showed a significant decrease. The morphological analysis showed good dispersion and adhesion of the PNSP to the PLA matrix. Based on the results of the characterization, biocomposites formulated with defatted PNSP have a potential to be used as sustainable fillers in PLA biocomposites. These biocomposites have a potential application as food containers, packaging trays, or disposable items.